Association of baseline white blood cell counts with tuberculosis treatment outcome: a prospective multicentered cohort study. (November 2020) - Chedid, Carole; Kokhreidze, Eka; Tukvadze, Nestani; Banu, Sayera; Uddin, Mohammad Khaja Mafij; Biswas, Samanta; Russomando, Graciela; Acosta, Chyntia Carolina Díaz; Arenas, Rossana; Ranaivomanana, Paulo PR.; Razafimahatratra, Crisca; Herindrainy, Perlinot; et al.
Highlights: Total white blood cell counts decrease during TB treatment. Lymphocyte proportions increase during TB treatment. Baseline lymphopenia and leukocytosis are associated with TB treatment failure. Future research should assess their stratifying value for failure risk in severe TB. Abstract: Objectives: Tuberculosis (TB) is the leading infectious cause of death in the world. Cheaper and more accessible TB treatment monitoring methods are needed. Here, we evaluated white blood cell (WBC) absolute counts, lymphocyte, and monocyte proportions during TB treatment, and characterized their association with treatment failure. Methods: This multicentered prospective cohort study was based in Bangladesh, Georgia, Lebanon, Madagascar, and Paraguay. Adult, non-immunocompromised patients with culture-confirmed pulmonary TB were included and followed up after two months of treatment and at the end of therapy. Blood counts were compared to treatment outcome using descriptive statistics, logistic regression, and Receiver Operating Characteristic (ROC) analyses. Results: Between December 2017 and August 2020, 198 participants were enrolled, and 152 completed treatment, including 28 (18.5%) drug-resistant patients. The rate of cure at the end of treatment was 90.8% (138/152). WBC absolute counts decreased, and lymphocyte proportions increased throughout treatment. In multivariate analyses, baseline high WBC counts and low lymphocyte proportions were associated with positive sputum culture results at the end of treatment (WBC > 11, 450 cells/mm 3 : p = 0.048; lymphocytes <16.0%: p = 0.039; WBC > 11, 450 cells/mm 3 and lymphocytes <16.0%: p = 0.024). Conclusion: High WBC counts and low lymphocyte proportions at baseline are significantly associated with the risk of TB treatment failure.